Insights into determinants of the activity of the flavodiiron NO reductase from Escherichia coli - Soares, Jéssica (2020)
"Flavodiiron proteins (FDPs) are a family of metalloproteins involved in the reduction of molecular oxygen and hydrogen peroxide to water and/or the reduction of nitric oxide to nitrous oxide. Bioinformatic analysis of the primary structure of the FDPs led to the identification of a conserved motif in class B FDPs (flavorubredoxins, FlRd), that is relatively close to the active centre. The present experimental work aimed to study the role played by two serines present in this motif in an FDP from E.coli. Thus, two mutants, S33D and S34D, were studied and characterized in order to determine the implications of such mutations on the biochemical, kinetic and spectroscopic properties of the enzyme. The production of the mutants was achieved in E. coli BL21 (DE3) Gold and it was found that the biochemical characteristics were kept almost unchanged.(...)"